Industrial Relations Practices in the Malaysian Public Sector: A Case Study of CUEPACS - Mat, Adnan (2023)
Industrial relations are a cornerstone in shaping the intricate dynamics between employees, employers, and government entities within a nation's labor landscape. This research paper embarks on a comprehensive exploration of industrial relations practices within Malaysia's public sector, casting a specific spotlight on the Congress of Unions of Employees in the Public and Civil Services (CUEPACS). The primary objective of this study, examining industrial relations practices in Malaysia's public sector from the vantage point of CUEPACS, is to gain a profound understanding, conduct a meticulous analysis, and shed light on the distinctive experiences, hurdles, and contributions of CUEPACS in molding industrial relations within this sector. Employing a qualitative research approach, the study navigates the intricate terrain of industrial relations in Malaysia's public sector through a single-case study framework. Qualitative interviews, taking the form of semi-structured conversations, stand as the linchpin of data collection. These dialogues unfold with senior trade union leaders representing a diverse tapestry of trade unions spanning various employment sectors, complemented by insights from a public representative. The research embarks on its journey by meticulously tracing the historical underpinnings of industrial relations in Malaysia, harking back to the colonial era when trade unions emerged as stalwart responses to exploitative labor practices. The study meticulously underscores key legislative landmarks and milestones that have left an indelible imprint on labor relations in the nation. Furthermore, the research meticulously dissects prominent industrial relations theories, including unitarism, pluralism, and the human resource management perspective. These theoretical frameworks act as prisms, elucidating the ideological foundations of industrial relations in Malaysia's public sector and their resonance with the objectives and endeavors of CUEPACS. The research delves deep into the distinctive challenges confronting Malaysia's public sector, including bureaucratic rigidity, political interventions, and the far-reaching impacts of globalization on the civil service workforce. These challenges serve as crucibles for comprehending CUEPACS' advocacy for the rights and well-being of public sector employees, furnishing valuable insights into the broader landscape within which the organization operates. Moreover, the research interweaves specific case studies and empirical research germane to industrial relations in Malaysia's public sector. These empirical narratives yield invaluable insights into the perspectives and experiences of public sector employees, their engagement with entities like CUEPACS, and the efficacy of collective bargaining mechanisms in addressing their concerns. This research serves as a clarion call, underscoring the paramount importance of grasping the intricacies of industrial relations within the public sector. Its significance extends beyond the realms of academia, encapsulating a pragmatic imperative for policymakers, trade union leaders, and public sector employees alike. This research lays a solid foundation for a deeper exploration of CUEPACS, with subsequent chapters poised to unfurl the organization's history, organizational structure, activities, and the formidable challenges it confronts while championing the interests of public sector workers. The findings of this study in Malaysia's public sector reverberate widely, laying the groundwork for a more profound comprehension of the role played by organizations like CUEPACS in shaping labor relations and advocating for the welfare of public sector employees. It cogently underscores the importance of proactive advocacy for employee rights, the adaptability of labor relations practices to evolving workforce dynamics, and the indelible impact of harmonious industrial relations on organizational triumph.